Bacterial adhesion of porphyromonas gingivalis on provisional fixed prosthetic materials - Mustafa Zortuk; Servet Kesim; Esma Kaya; Hatice Ozbilge; Kerem Kilig; Ozlem colgegen (Wolters Kluwer Medknow Publications, 2010)
Background: When provisional restorations are worn for long term period, the adhesion of bacteria becomes a primary factor in the development of periodontal diseases. The aims of this study were to evaluate the surface roughness and bacterial adhesion of four different provisional fixed prosthodon-tic materials. Methods: Ten cylindrical specimens were prepared from bis-acrylic composites (PreVISION CB and Protemp 3 Garant), a light-polymerized composite (Revotek LC), and a polymethyl methacrylate-based (Dentalon) provisional fixed prosthodontic materials. Surface roughness was assessed by profilometry. The bacterial adhesion test was applied using Porphyromonas gingivalis (P. gingivalis) and spectro-fluorometric method. Statistical analysis was performed using ANOVA and Dunnett t-tests. Results: All tested materials were significantly rougher than glass (P < 0.05). Revotek LC had the greatest fluorescence intensity, PreVISION and Protemp 3 Garant had moderate values and all of them had significantly more bacterial adhesion compared to glass (P < 0.05). Dentalon had the lowest fluorescence intensity among the provisional fixed prosthodontic materials. Conclusion : The quantity of bacterial adhesion and surface roughness differed among the assessed provisional fixed prosthodontic materials. The light-polymerized provisional material Revotek LC had rougher surface and more bacterial adhesion compared with the others.